2014
DOI: 10.4172/2155-6113.1000308
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Burden of Human Immunodeficiency Virus and Hepatitis B Virus Co-infection in Nigeria: A Systematic Review and Meta-Analysis

Abstract: The impact of co-infection is particularly important in places with widespread use of antiretroviral therapy. As the use of ART increasingly becomes prevalent in certain regions of the world with high HBV endemicity and as long term survival increases, It is likely

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
34
1
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(36 citation statements)
references
References 51 publications
0
34
1
1
Order By: Relevance
“…Furthermore, according to a study conducted among 102 HIV infected persons in Lagos, comprising of 32 males and 70 females, it was discovered that 29 patients representing 28.4% of the recruited sample were co-infected with HBsAg [37]. According to a comprehensive meta-analysis by Owolabi, et al [19] of HBV/HIV co-infection of studies in the six geopolitical zones of Nigeria, there was an overall 15% prevalence rate.…”
Section: R E T R a C T E Dmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, according to a study conducted among 102 HIV infected persons in Lagos, comprising of 32 males and 70 females, it was discovered that 29 patients representing 28.4% of the recruited sample were co-infected with HBsAg [37]. According to a comprehensive meta-analysis by Owolabi, et al [19] of HBV/HIV co-infection of studies in the six geopolitical zones of Nigeria, there was an overall 15% prevalence rate.…”
Section: R E T R a C T E Dmentioning
confidence: 99%
“…Interestingly, studies have been carried out to find out the prevalence rate of HIV/HBV co-infections in Nigeria [17] [18] [19] [20], however, there is a paucity of research on the knowledge of citizens about the co-infection in Nigeria. This study, therefore, seeks to find out the use of information source as well as the knowledge on HIV/HBV co-infection among Lagos residents, Southwest Nigeria.…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of HBV among patients with the acquired immunodeficiency virus (HIV) infection varies widely in Nigeria depending on the study population [9] . However, a meta-analysis of 33 studies from Nigeria yielded an HBV pooled prevalence of 15% (95% CI: 13-17) among such individuals [9] .…”
Section: Introductionmentioning
confidence: 99%
“…In Nigeria, the global burden of cancer in 2013 shows liver cancer to be the commonest cause of cancer death (Naghavi, 2015). HBV infection is also highly endemic in Nigeria as about 75% of the Nigerian population may have been exposed to HBV at one time or the other in their life and an estimated 12% of the total population have chronic carriage of HBV (Owolabi et al, 2014;Sirisena et al, 2002) and is reported to be the most common cause of liver disease (Musa et al, 2015). With high rates of blood transfusion following road traffic accidents, pregnancy and its complications, malaria and sickle cell diseases (in addition to more recognized risk factors, such as intravenous drug usage, unprotected sexual intercourse and poor sterilization of surgical or dental equipment), it is not surprising to see the prevalence of HBV infection over 30% in some regions of the country (Luka et al, 2008;Mbaawuaga et al, 2008).…”
Section: Introductionmentioning
confidence: 99%